Cardiovascular positron emission tomography imaging of fibroblast activation: A review of the current literature - Loganath, Krithika; Craig, Neil; Barton, Anna; Joshi, Shruti; Anagnostopoulos, Constantinos; Erba, Paola Anna; Glaudemans, Andor W.J.M.; Saraste, Antti; Bucerius, Jan; Lubberink, Mark; Gheysens, Olivier; Buechel, Ronny R.; et al. (Elsevier BV, 2025)
Fibrosis is one of the key healing responses to injury, especially within the heart where it helps to maintain structural integrity following acute insults such as myocardial infarction. However, if it becomes dysregulated then fibrosis can become maladaptive leading to adverse remodelling, impaired cardiac function and heart failure. Fibroblast activation protein is exclusively expressed by activated fibroblasts, the key effector cells of fibrogenesis, and has a unique extracellular domain that is an ideal ligand for novel molecular imaging probes. Fibroblast activation protein inhibitor (FAPI) radiotracers have been developed for PET imaging, demonstrating high selectivity for activated fibroblasts across a range of different pathologies and disparate organ systems. In this review, we will summarize the role of fibroblast activation protein in cardiovascular disease and how FAPI radiotracers might improve the assessment and treatment of patients with cardiovascular diseases.